A New gcrR-Deficient Streptococcus mutans Mutant for Replacement Therapy of Dental Caries - Wenting Pan; Tiantian Mao; Qing-an Xu; Jin Shao; Chang Liu; Mingwen Fan (The Scientific World Journal)
Background. gcrR gene acts as a negative regulator related to sucrose-dependent adherence in S. mutans. It is constructive to test the potential capacity of mutans with gcrR gene deficient in bacteria replacement therapy. Methods. In this study, we constructed the mutant by homologous recombination. The morphological characteristics of biofilms were analyzed by confocal laser scanning microscopy. S. mutans UA159 and the mutant MS-gcrR-def were inoculated, respectively, or together for competitive testing in vitro and in rat model. Results. Adhesion assay showed that the adhesion ability of the mutant increased relative to the wild type, especially in the early stage. MS-gcrR-def out-competed S. mutans UA159 in vitro biofilm, and correspondingly coinfection displayed significantly fewer caries in vivo. The former possessed both a lower level of acid production and a stronger colonization potential than S. mutans UA159. Conclusion. These findings demonstrate that MS-gcrR-def appears to be a good candidate for replacement therapy.